The influence of metakaolin on the autogenous and drying shrinkage of internally cured concrete - Tsivolas Konstantinos; Bekes Epameinondas; Badogiannis Efstratios (MATEC Web of Conferences)
Internal curing might be considered crucial for applications, where High-Performance Concrete (HPC) mixtures are needed, to mitigate or even eliminate the development of autogenous shrinkage and thus the formation of early-age microcracks that diminish the durability of concrete. Lightweight aggregates act as a water reservoir that provides water to unhydrated cement particles when needed, has already been proven an effective curing mechanism. On the other hand, adding supplementary cementitious materials could be a subsidiary strategy to prevent autogenous shrinkage, although in some cases opposite results were reported. Even though metakaolin is well known for its pozzolanic activity and contribution to enhancing concrete’s mechanical and durability properties, its effect on autogenous shrinkage needs further investigation. This research examines the individual effects of pumice and metakaolin, as well as their combined influence on autogenous and drying shrinkage. The findings indicate that while metakaolin slightly increases early-age shrinkage, it contributes to a reduction in drying shrinkage at later stages.